Raman scattering owing to magneto-polaron states in monolayer transition metal dichalcogenides - C. Trallero-Giner; D. G. Santiago-Pérez; D. V. Tkachenko; G. E. Marques; V. M. Fomin (Scientific Reports)
Abstract Magneto-optical measurements are fundamental research tools that allow for studying the hitherto unexplored optical transitions and the related applications of topological two-dimensional (2D) transition metal dichalcogenides (TMDs). A theoretical model is developed for the first-order magneto-resonant Raman scattering in a monolayer of TMD. A significant number of avoided crossing points involving optical phonons in the magneto-polaron (MP) spectrum, a superposition of the electron and hole states in the excitation branches, and their manifestations in optical transitions at various light scattering configurations are unique features for these 2D structures. The Raman intensity reveals three resonant splittings of double avoided-crossing levels. The three excitation branches are present in the MP spectrum provoked by the coupling of the Landau levels in the conduction and valence bands via an out-of-plane $$A_1$$ A 1 -optical phonon mode. The energy gaps at the anticrossing points in the MP scattering spectrum are revealed as a function of the electron and hole optical deformation potential constants. The resonant MP Raman scattering efficiency profile allows for quantifying the relative contribution of the conduction and valence bands in the formation of MPs. The results obtained are a guideline for controlling MP effects on the magneto-optical properties of TMD semiconductors, which open pathways to novel optoelectronic devices based on 2D TMDs.